Pro Tools LE 7 ignite! - Andrew Hagerman (Course Technology., 2008)
Get ready to explore the world of computer music creation with Pro Tools LE 7! Even if you've never created music on your computer, Pro Tools LE 7 Ignite!, Second Edition will give you the skills you need to record and mix with confidence. Completely updated to cover the new features of Pro Tools LE 7.3 and 7.4, the book presents everything you need to know about this amazing digital audio workstation with easy-to-follow clarity and screen shots that make it easy to dive into the features. Begin with the basic techniques of recording, editing, and mixing MIDI and digital audio. Then, get ready to harness the power of Pro Tools as you explore software effects, virtual instruments, and mixes that you can automate and edit with some of the best tools in the business. Ignite your music with the power of Pro Tools LE 7.4!